A Phenomenological Study of International Students’ Adaptation to Cultural Diversity - Mahendra, Muhammad Izal; Maulina, Maulina; Nasruullah, Rahmat; S, Tasman (Journal of English Language and Education, 2026)
In an era of increasing global student mobility, understanding cross-cultural adaptation is essential to ensure international students’ academic success, psychological well-being, and social integration. However, limited studies specifically explore Indonesian students’ lived experiences in short-term credit transfer programs within Southeast Asian contexts. This study investigates Indonesian students in the International Credit Transfer (ICT) program and their cross-cultural adaptation to cultural diversity in the Philippines. Using a qualitative phenomenological approach, data were collected through in-depth semi-structured interviews and analyzed thematically. The findings reveal that adaptation is a gradual process influenced by personal communication, host and ethnic interactions, environmental factors, and individual predispositions. Although students initially experienced language anxiety and low confidence, continuous English exposure, buddy systems, and inclusive campus environments facilitated academic and social adjustment. Ethnic networks provided emotional support while enabling integration with the host culture. The study highlights the importance of institutional support and individual readiness in promoting successful cross-cultural adaptation.